2019
DOI: 10.1029/2018jb017067
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Red Bed Magnetization Constrained by Fluvial Intraclasts

Abstract: The magnetization of hematite-bearing sedimentary rocks provides critical records of geomagnetic reversals and paleogeography. However, the timing of hematite remanent magnetization acquisition is typically difficult to constrain. While detrital hematite in sediment can lead to a primary depositional remanent magnetization, alteration of minerals through interaction with oxygen can lead to the postdepositional formation of hematite. In this study, we use exceptionally preserved fluvial sediments within the 1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 52 publications
(81 reference statements)
7
37
0
Order By: Relevance
“…In samples retaining the DRM from both the Gongjue and Nangqian basins, DRM carried by detrital hematite unblocks between 600°C and 680°C (Figures 2a-2d, 2g, and 2h), corresponding to hematite grain sizes of >240 nm. These observations support that hematite carrying the CRM has a wide distribution of grain size and unblocking temperature spectra, while hematite carrying the DRM is usually coarse and has confined unblocking temperature spectrum due to hydrodynamic sorting (Jiang et al, 2015;Swanson-Hysell et al, 2019). The contribution of detrital (titano)magnetite to the NRM is low in the remagnetized red beds (Figure 4), and its signal is probably swamped by the authigenic hematite with a broad unblocking temperature spectra.…”
Section: 1029/2020jb020068supporting
confidence: 65%
See 1 more Smart Citation
“…In samples retaining the DRM from both the Gongjue and Nangqian basins, DRM carried by detrital hematite unblocks between 600°C and 680°C (Figures 2a-2d, 2g, and 2h), corresponding to hematite grain sizes of >240 nm. These observations support that hematite carrying the CRM has a wide distribution of grain size and unblocking temperature spectra, while hematite carrying the DRM is usually coarse and has confined unblocking temperature spectrum due to hydrodynamic sorting (Jiang et al, 2015;Swanson-Hysell et al, 2019). The contribution of detrital (titano)magnetite to the NRM is low in the remagnetized red beds (Figure 4), and its signal is probably swamped by the authigenic hematite with a broad unblocking temperature spectra.…”
Section: 1029/2020jb020068supporting
confidence: 65%
“…The concave and convex shape of the thermal decay curves is thus proposed to indicate CRM and DRM, respectively (Jiang et al, 2015). Uncertainty still exists, however, in the use of this criterion because paleomagnetic studies on natural samples reveal that the unblocking temperature spectra of the CRM can overlap with those of the DRM and extend up to the Néel temperature of hematite (Jiang et al, 2017; Swanson‐Hysell et al, 2019). In a recent study of the Paleogene red beds in the Nangqian Basin (eastern Tibetan Plateau), we have identified that remagnetized red beds contain large amounts of nanogoethite, whereas goethite is not present in red beds retaining the DRM (Huang, Jackson, Dekkers, Solheid, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…7). In these cases, it is possible that a chemical remanent magnetization, generated through oxidation of magnetite by orogenic hydrothermal fluids, has overprinted the primary detrital remanent magnetization completely [ 34 , 35 ]. The HTCs are considered the primary magnetization in all our sections; they are carried by detrital hematite and show dual polarities (Supplementary Figs 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the remanent coercivity on the lower end of hematite's range, we suggest that this hematite is either very fine grained (<1 μm) or very large grained (>50 μm) (Özdemir & Dunlop, ; Peters & Dekkers, ). Nanophase hematite has been shown to form in diagenetic processes either during early diagenesis through aging of ferrihydrite or through secondary diagenetic processes repartitioning iron, for example from iron‐bearing carbonates and silicates (Jiang et al, ; Swanson‐Hysell et al, ; Walker et al, ; Weil & Van der Voo, ).…”
Section: Results and Mineralogy Interpretationmentioning
confidence: 99%